Minor Cannabinoids of Cannabis sativa L. - Thomas, Fabian Johannes; Kayser, Oliver (Journal of Medical Science, 2019)
Cannabinoids from Cannabis sativa L. play an important role as natural products in clinics. The major cannabinoids compromise tetrahydrocannabinolic acid (THCA) and cannabidiolic acid (CBDA) and its decarboxylated analogs. In this review, we focus on often neglected minor cannabinoids and discuss biosynthetic and chemical degradation routes to other neglected cannabinoids in Cannabis sativa starting from THCA, CBDA and cannabichromenic acid (CBCA). Based on the literature, patents and scientific reports, essential routes for the chemical modification of cannabinoids are discussed to explain chemical diversity chemical conversion and degradation by UV light, as well as temperature and pH leading to the formation of structurally unusual cannabinoids in planta called as minor cannabinoids. Based on known bioorganic reaction schemes and organic chemistry, principles for minor cannabinoid formation like [2+2] cycloaddition, Markonov condensation, radical introduction, or aromatization are discussed. Finally, the non-aqueous environment in Cannabis sativa trichomes is analyzed to clarify their role of a miniaturized bioreactors the light-induced conversion in  a non-aqueous enviroment. The overall objective is to bridge from metabolic profiling via cannabinomics to structural and chemical diversity that allows the definition of patterns with consequences also to pharmacology and plant breeding.